Power and morality. (December 2015) - Lammers, Joris; Galinsky, Adam D; Dubois, David; Rucker, Derek D
Highlights: The link between power and morality is complex. Power causes disinhibition; disinhibition can strengthen immoral and moral impulses. Power affects self-focus and thus unethical propensities toward self and others. Power can both undermine and elevate morality. Abstract : This review synthesizes research on power and morality. Although power is typically viewed as undermining the roots of moral behavior, this paper proposes power can either morally corrupt or morally elevate individuals depending on two crucial factors. First, power can trigger behavioral disinhibition. As a consequence, power fosters corruption by disinhibiting people's immoral desires, but can also encourage ethical behavior by amplifying moral impulses. Second, power leads people to focus more on their self, relative to others. Thus, those with power are more likely to engage in self-beneficial behavior, but those who lack power are more prone to engage in other-beneficial unethical behavior. Overall, we offer predictions as to when and why power will yield more or less moral behavior.